STUDIES OF LYMPHOCYTE SUBSETS IN PATIENTS WITH A MIXED INFECTION CAUSED BY THE VIRUSES FROM HERPESVIRIDAE FAMILY - T. I. Dolgikh; T. F. Sokolova; E. Y Minakova (Медицинская иммунология, 2014)
Present work deals with specific immunologic changes that are typical to various types of mixed infection caused by viruses from Herpesviridae family during their activation phase. These changes include increased amounts of CD3+/CD25+ lymphocytes and CD3+/CD4+ cells, decreased levels of CD3+/CD95+ cells, increased contents of natural killer cells, altered interrelations between the immune system parameters. Involvement of cytomegalovirus or Epstein-Barr virus (EBV) in the mixed infection is associated with some special changes of the lymphocyte subsets. I.e., a co-infection with herpes virus simplex (HSV) type 1/2 and cytomegalovirus is characterized by increased amounts of activated T-lymphocytes and T-helper cells, whereas mixed HSV/EBV infection is accompanied by sharp reduction in CD3+/CD95+ lymphocytes.